Analysis of Characteristics and Consumer Satisfaction in Buying Fruits in Bende Village, Kadia District, Kendari City - Dedi Syafrin; Surni; Samsul Alam Fyka (International journal of technology and education research, 2026)
This study aims to (1) Identify the characteristics of fruit consumers in Bende Village, Kadia District, Kendari City, (2) Analyze the level of consumer satisfaction in buying fruits in Bende Village, Kadia District, Kendari City. The method used in this research is quantitative method using Customer Satisfaction Index (CSI). The population in this study were all consumers who purchased fruits at the Bende Village fruit market, Kadia District, Kendari City. Determination of respondents is done accidentally (Accidental Sampling). Accidental Sampling method is a sampling technique based on coincidence of members of the population who are encountered and willing to be respondents so that they are sampled, with a total sample of 36 people. The results showed that (1) The characteristics of respondents based on gender in buying fruits are mostly male as many as 23 people or 63%, characteristics based on age, namely at the age of 15-25 years as many as 15 people or 42%, characteristics based on the length of education for 12 years as many as 25 people or 69%, characteristics based on status dominated by unmarried as many as 25 people or 56%, characteristics based on the respondent's job as self-employed as many as 14 respondents or 39%, characteristics based on respondent income as much as <Rp 500.000 with 14 respondents, this is because the majority who buy fruit work as housewives or their income is still from the head of the household (husband). (2) The level of consumer satisfaction obtained a figure of 0.76 or 76%. This figure is in the satisfied criteria because it is in the range 0.66 - 0.80. This shows that consumers are satisfied with the performance of the attributes of the variable quality of fruits and service quality when shopping for fruits.